2023
DOI: 10.2188/jea.je20210338
|View full text |Cite
|
Sign up to set email alerts
|

Work and Family Conflicts, Depression, and “Ikigai”: A Mediation Analysis in a Cross-cultural Study Between Japanese and Egyptian Civil Workers

Abstract: Background: Total work-family conflicts (TWFCs) could associate with mental health, and having ikigai (a purpose of life) may mediate this association. Methods: In a cross-cultural study of 4,792 Japanese Aichi Workers' Cohort study participants and 3,109 Egyptian civil workers, the Midlife Development in the United States (MIDUS) questionnaire measured TWFCs and the Center for Epidemiological Studies Depression (CES-D) 11-item scale measured depression. We used logistic regression models to estimate odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Despite the observed gender difference in the prevalence of W_F_Cs and poor self-rated health, our results are in line with the previous research showing associations of W_F_Cs and its two forms, WFC and FWC, with poor self-rated health of both genders in Japan [8,13,23], Egypt [12], and other populations [4,22,24,32]. Increased inter-role conflicts between work and family domains can reduce the time for sleep [28] or leisure activities, thus increasing psychological stress [9] and affecting physical [3] and mental [11,14,15] health conditions.…”
Section: The Reported Self-rated Health Status and Its Associations W...supporting
confidence: 91%
See 2 more Smart Citations
“…Despite the observed gender difference in the prevalence of W_F_Cs and poor self-rated health, our results are in line with the previous research showing associations of W_F_Cs and its two forms, WFC and FWC, with poor self-rated health of both genders in Japan [8,13,23], Egypt [12], and other populations [4,22,24,32]. Increased inter-role conflicts between work and family domains can reduce the time for sleep [28] or leisure activities, thus increasing psychological stress [9] and affecting physical [3] and mental [11,14,15] health conditions.…”
Section: The Reported Self-rated Health Status and Its Associations W...supporting
confidence: 91%
“…On the other hand, participants should have been ranked weak in at least one form of conflict while ranked moderate in the other form of conflict to be in the weak total W_F_Cs category. Other than these, participants were ranked moderate in the total W_F_Cs [14,29]. We computed the odds ratios (ORs) and 95% confidence intervals (CIs) of having poor self-reported health across the increasing categories of the conflicts, age groups, smoking status, alcohol drinking status (for Japanese only), and quartiles of physical activity using the weak category of conflict, age ≤ 30 years, never smokers, never drinkers, and the lowest quartile of physical activity respectively as the reference groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the dimension "restrictive emotionality" is higher in depressed men is in accordance with a study by Honkalampi et al (2000), which showed that the prevalence of alexithymia (the inability to recognize and verbalize emotions) was eight times higher in depressed participants than in healthy subjects. In addition, it was shown that depressed men report more conflicts between work and family life (Eshak et al, 2023). Overall, one can assume that men with more psychological distress also exhibit more GRC in general, which is supported by the strong correlations between GRC measures and depression severity measures (O'Neil, 2013).…”
Section: Tmi and Grcmentioning
confidence: 87%